2013
DOI: 10.1080/09712119.2013.822806
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameter estimates for growth traits in Iran-Black sheep

Abstract: The present study was conducted to estimate variance components and genetic parameters for growth traits of Iran-Black sheep, maintained at the Abbasabad sheep breeding station, located in northeast of Mashhad, (Razavi Khorasan province of Iran) over a period of 24 years (1981 through 2004). Records of 4607 lambs descended from 155 rams, and 1227 ewes were used in the study. Traits included for the present study were birth weight (BW), weaning weight (WW), weight at 6 months (W6), weight at 9 months (W9), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
5
8
0
Order By: Relevance
“…The variation in results among different studies, even within the same breed, is justified by the fact that the weights at birth and weaning are greatly influenced by different environmental effects, especially the maternal environment (KAMJOO et al, 2014), and by the management adopted on each farm. In the present study, some factors that probably influenced lamb performance were reproductive management, the supplementation of the dams before lambing, and the use of creep feeding for the lambs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in results among different studies, even within the same breed, is justified by the fact that the weights at birth and weaning are greatly influenced by different environmental effects, especially the maternal environment (KAMJOO et al, 2014), and by the management adopted on each farm. In the present study, some factors that probably influenced lamb performance were reproductive management, the supplementation of the dams before lambing, and the use of creep feeding for the lambs.…”
Section: Resultsmentioning
confidence: 99%
“…The positive and moderate correlation observed between BW and WW was also expected, as the dams received supplemented feed during part of the pregnancy and the lambs had access to creep feeding before weaning. Many publications have reported moderate to high positive correlations between these two traits in different sheep breeds (HANFORD et al, 2003;BARROS et al, 2004;EL-AWADY, 2011;SAVAR-SOFLA et al, 2011;KAMJOO et al, 2014 EKIZ (2005), in mammalian species, growth traits, in particular until weaning, are substantially influenced by the environment provided by the dam.…”
Section: Resultsmentioning
confidence: 99%
“…Mating ratio was one breeding ram to 10-12 ewes. Lambing began in mid-January and ended in February (Kamjoo et al, 2014). Lambs were weighed and ear-tagged shortly after birth and weaned at 90 days of age.…”
Section: Data and Flock Managementmentioning
confidence: 99%
“…Further, to design the effective selection programs for improving the efficiency of ewe production, the knowledge of genetic parameters for ewe traits and the genetic relationships among the traits are of significant importance. Therefore, estimates for genetic parameters, selection criterion, response to selection, and construction of selection indexes are needed (Kamjoo, Baneh, Yousefi, Mandal, & Rahimi, 2014). Previous studies have shown that reproductive traits are not only influenced by the genes of the individual and the environment in which it is raised, but also by the service sire and the maternal environment (Maghsoudi, Torshizi, & Jahanshahi, 2009;Mokhtari, Rashidi, & Esmailizadeh, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, effects of the lamb weight and age of the ewe were found to be important for the reproductive performance of ewes and for the lamb's growth rate (ACTAŞ et al, 2015). Body weight and growth traits of lambs are known to be affected by the direct and maternal genetic effects as well as by environmental effects (KAMJOO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%